OPTIMIZING OIL VESSEL TERMINAL LAYOUT: A COMPREHENSIVE LITERATURE REVIEW - Filemon, F; Gumelar, Fajar; Nugroho, Setyo (Marine & Earth Science and Technology Research Center, DRPM, ITS, 2023)
This research paper systematically explores oil vessel terminal layout optimization, emphasizing safety considerations, environmental impact assessment, and efficient infrastructure design. The study employs a comprehensive methodology involving literature review and data synthesis, delving into technical and organizational safety aspects, safety exclusion zones, and the key components comprising an oil vessel terminal layout. By providing a holistic overview and a visual representation of terminal infrastructure, this research contributes to a deeper understanding of the complexities involved, offering valuable insights for industry practitioners and future research endeavours in this domain.